2021
DOI: 10.1002/ppul.25301
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary dysplasia as a determinant of respiratory outcomes in adult life

Abstract: Respiratory disease is unfortunately common in preterm infants with the archetype being bronchopulmonary dysplasia (BPD). BPD affects approximately 50,000 preterm infants in the U.S. annually with substantial morbidity and mortality related to its pathology (alveolar, airway, and pulmonary vasculature maldevelopment). Predicting the likelihood and severity of chronic respiratory disease in these children as they age is difficult and compounded by the lack of consistent phenotyping. Barriers to understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 93 publications
0
30
0
1
Order By: Relevance
“…This is of special interest, because preterm infants accumulate significant growth deficits by the time of discharge from hospital 31,32 that persist through infancy and early childhood into adolescence. 33,34 Our subgroup analyses prevailed that ELBW and SGA infants with the highest risk for growth deviations benefited in somatic growth when their feedings are advanced rapidly using STENA. Additionally, our ROC analysis calculation indicates that standardized and progressive feeding works even…”
Section: Discussionmentioning
confidence: 91%
“…This is of special interest, because preterm infants accumulate significant growth deficits by the time of discharge from hospital 31,32 that persist through infancy and early childhood into adolescence. 33,34 Our subgroup analyses prevailed that ELBW and SGA infants with the highest risk for growth deviations benefited in somatic growth when their feedings are advanced rapidly using STENA. Additionally, our ROC analysis calculation indicates that standardized and progressive feeding works even…”
Section: Discussionmentioning
confidence: 91%
“…The likelihood of adverse outcomes with respiratory viral infections in infancy is increased with a history of preterm lung disease [94]. Respiratory infections may alter subsequent lung function through adverse effects on immune responses, chronic pathogen colonization, or microbiome changes, and injury repair [95]. A national study from Taiwan reported that a history of BPD was associated with a 1.8-14.4-fold increased risk of hospitalization for respiratory syncytial virus (RSV) compared to gestation and age-matched controls [80].…”
Section: Infectionmentioning
confidence: 99%
“…Bronchopulmonary dysplasia (BPD) has remained the most significant respiratory complication of prematurity more than 50 years after its original description by Northway et al 1 Since then the clinical course of BPD has become milder due to the significant development in the management of premature infants, 2,3 however, the manifestations of this chronic respiratory disease may persist through the lifespan and can be detected on various measures of lung function 4 . Although anti‐inflammatory corticosteroids (CSs) have long been used for the prevention and treatment of BPD, their therapeutic efficacy and long‐term neurodevelopmental and respiratory consequences still need to be evaluated 2,3 …”
Section: Introductionmentioning
confidence: 99%